Pronunciation Problems of Indonesian EFL Learners: An Error Analysis - Ronald Maraden Parlindungan Silalahi (Universitas Bunda Mulia, 2017)
Mispronunciation is the act of pronouncing linguistic expression incorrectly or unconventionally. In English as Foreign Language (EFL) context, it has become the concern for it can lead to miscommunication, misunderstanding, and misperception among participants. In Indonesian pedagogical context, English Language Teaching (ELT) is more focused on improving students’ mastery of grammar without considering the pronunciation. This research is aimed to analyze English learners’ ability to pronounce English words. The research is conducted with 30 English Language and Culture student respondents of Universitas Bunda Mulia. Keywords: mispronunciation, phonetics, English language teaching